Conflict resolution in Asia mediation and other cultural models - Stobbe, Stephanie Phetsamay (Conflict resolution and peacebuilding in Asia., 2018)
"Examines the role of mediation and other cultural conflict resolution models in Asia. the contributors use various countries as case studies to analyze how traditional, Indigenousenous, and culturally based conflict resolution processes interact with more formal legal systems to address conflicts" --Provided by publisher